Design of novel microwave-heated reaction cells for infrared spectroscopy - Silverwood, Ian P. (University of Edinburgh; College of Science and Engineering; School of Chemistry, 2006)
Two novel microreactor cells for the investigation of catalysts by in-situ infrared spectroscopy under microwave and conventional heating are presented. A transmission infrared microreactor cell is demonstrated which holds a pressed catalyst disc in a controlled atmosphere and allows study of reactions from ambient temperatures to over 473 K. A cell that allows diffuse reflectance spectroscopy under reaction conditions up to 373 K under microwave heating and 423 K under conventional heating is also described. The optical characteristics of these cells are determined by the choice of CaF2 as the window material, allowing transmission from 77000-1110 cm−1. An oscillating microwave power heating regime was used to study the oxidation of carbon monoxide in air over the supported platinum catalysts EUROPT-1 and EUROPT-3, and their support oxides in these cells. The reaction was followed by time-resolved infrared spectroscopy and mass spectrometry. Both displayed a number of features that oscillated with the same frequency as the microwave perturbation. Production of CO2 appeared to vary with temperature in the same manner whether the catalysts were heated conventionally or with microwave radiation. Although no specific microwave effect for this reaction was observed, accurate thermometry within the cells was limited through the constraints imposed by microwave heating. Preliminary infrared emission and liquid phase experiments using the transmission cell are also reported.
The design of novel microwave-heated reaction cells for infrared spectroscopy
Keywords: infrared spectroscopy; microwave